The Relationship between the Addiction of Social Networks with Lifestyle and Communication with Parents - Sorraya Zamen-Yamchi; Zohreh Sayyadpour (Shahid Beheshti University of Medical Sciences, 2018)
Background and Objective: The development of new technologies has affected the relationship between individuals and their lifestyles. The purpose of this study was to determine the relationship between addiction to social networks and lifestyle and communication with parents. Materials and Methods: The research method was correlation. Of the 2nd, 9th and 16th grade students of secondary girls' schools in Tehran (10th to 12th grades) who were studying in the academic year of 2016-17, 200 were selected by multi-stage cluster sampling method. Questionnaires, social network addiction researcher, standard lifestyle questionnaire, and Smith's questionnaire and parent-child relationship questionnaire. The findings were analyzed using Pearson correlation test and regression and analyzed using SPSS.18 software. Results: The mean (SD) age of students was 16.9 (2.2). The results showed that there was a negative relationship between the mean (SD) of addiction to social networking was 41.1 (17.5) with relation to father 104.9 (31.5) (r =-0.32, P<0.01), relation with mother was 120.4 (27.3) (r =-0.26, P<0.01), and relation with parents 112.8 (27) (r =-0.31, P<0.01) this means that as addiction to social networks increases, the relationship with the parent decreases but there was no relationship between addiction to social network with life style 45.2 (8.7) (r = 0.08, P>0.05). Conclusion: It can be concluded that social networking was associated with communication with the father, the relationship with the mother and the relationship with the parents, but there was no relationship between the social networks with the lifestyle. DOI: http://doi.org/10.22037/ch.v6i1.20151